EKSEKUSI JAMINAN KREDIT BERUPA KIOS PASAR OLEH BANK - Hardianto, Tri; Nasution, Krisnadi; Setiadji, Sri (Yayasan Akrab Pekanbaru, 2019)
The bank is an intermediary institution, meaning that its main activities are raising funds and channeling funds to the public. The funds withdrawn from the community are then channeled back to the community in the form of credit. Lending is generally done by entering into an agreement.